G284(P) Final year medical student use and acceptability of an e-learning module in a paediatric subspecialty. (7th April 2014) - Southwood, TR; Rainger, P; Couperthwaite, J; Hussain, D; Perryer, DG
Abstract : Traditional medical student learning and teaching methods, such as lectures and bedside teaching, maybe inadequate for providing core knowledge and clinical skills in paediatrics, with reduction in undergraduate time allocated to paediatrics and increasing medical student numbers. To supplement paediatric knowledge and improve access to essential clinical skills, we developed an e-learning module, "paediatric rheumatolog-e", within a Canvas © learning management system. The design promoted revision of basic sciences (e.g. musculoskeletal anatomy, inflammation and immunological processes), in the context of clinical sciences (e.g. pharmacology, rheumatology and child development). Learning content comprised videos of patient and family narratives, clinical skills and layered information on 4 key learning outcomes: joint swelling, limb pain, back pain and the limping child. Optional information on juvenile idiopathic arthritis was provided. Core knowledge was consolidated using interaction, reflection and formatively assessed case-based quizzes. Purpose: The aim of this study was to assess final year medical student use and acceptabilty of an e-learning module in paediatric rheumatology. Methods: 341 final year medical students were notified of the e-learning module by email at the beginning of the academic year, and again 3 months later. Students beginning their paediatric rotation were reminded in the introductory lecture and written course materials. Use of the module was assessed 4 months into the academic year, after 3 blocks of medical students (193 students, 53% of the year) had undertaken a paediatric rotation. Canvas (c) embedded in-course analytics were used and acceptability was ascertained through online feedback and an email questionnaire. Results: 187 students (55%) accessed the e-learning module (a mean of 14.8 pages per student, range 1–270, 28% >3); of these 20 (11%) answered at least one clinical quiz. Higher median quiz scores were found in the joint swelling quiz and back pain quiz. There was a preference for accessing the module during a paediatric rotation (74/193 students to date, 62%). Time for completion of the module was 1–1.5 h. Student acceptability was high, with comments such as "thorough" and "engaging", and requests for more e-learning modules. Conclusion: An e-learning module in a paediatric speciality was widely used and found to be acceptable by final year medical students.